In situ conservation and stock enhancement of endemic fish resources through captive breeding and artificial sanctuaries - PADMAKUMAR, K G; BINDU, L; MANU, P S (The Indian Journal of Animal Sciences, 2010)
Pearlspot, Etroplus suratensis and Golden catfish Horabagrus brachysoma, are endemic to Peninsular India, facing serious depletion in the Vembanad wetlands due to environmental alterations. In order to develop viable breeding techniques of these species under controlled conditions, habitat requirements and critical reproductive traits were closely monitored. Both the species are omnivorous, the former is an asynchronous spawner while the latter a group synchronous spawner. Breeding behaviour of the species were closely observed in natural and experimental conditions and based on this, captive breeding protocols were developed. E. suratensis was successfully bred under controlled conditions in artificial raceways of 70 m2. The percentage success of breeding in the devised system (71%) was higher than that of pond breeding. Hatchling survival was also higher in the larval rearing system. Induced breeding of H. brachysoma was carried out by the administration of Ovaprim @1ml. kg-1 body weight or fish pituitary extract @50-60 mg.kg-1 body weight, the former being more effective. Fertilisation upto 100% and hatching rate of 73.1% were obtained. The present investigations on captive breeding is a major advance towards development of a standardized mechanism for conservation of indigenous species.